The Corporeal Identity When the Self-Image Hurts - Faccio, Elena; SpringerLink (Online service) (New York, NY : Springer New York : Imprint: Springer, 2013)
Why do so many people feel uneasy when they look in the mirror or see pictures of themselves? The contrast between their body and the way they imagine it to be, or the way they wish it were, may account for their malaise. This contrast might even be the starting point for various kinds of psychological disorders. If a person$1 (Bs self-image fails to match up to their vision of the body they would rather have, that person may experience feelings of dissatisfaction and low self-esteem, deeply wounding his or her self-identity. The more physical appearance becomes the calling card for those who seek the approval of others, the truer this fact becomes. The Corporeal Identity: When the Self-Image Hurts, written by a committed university researcher and psychologist, successfully elaborates concepts drawn from a variety of disciplines an draws on professional experience largely dedicated to exploring disorders wherein body identity is the chosen field for communication and exchange.s
Keywords: Philosophy (General).; Psychiatry; Psychology, clinical; Consciousness; Psychology; Health Psychology; Psychiatry; Sociology, general; Personality and Social Psychology